Insincere promises : the law of misrepresented intent - Ayres, Ian, 1959- (Yale University Press, 2005)
The authors explore what promises say from the perspectives of philosophy. economics & the law. They identity four chief mistakes that courts make in promissory fraud cases, & they offer a theory for how courts & practitioners should handle promissory fraud cases.